(untitled) (Research in Agriculture Livestock and Fisheries, 2024)
Vegetables are heavily sprayed and prone to retaining residues. The Department of Agriculture Extension (DAE), Bangladesh has set up some projects to disseminate technologies among the farmers to reduce pesticide residues. Farmers are motivated to produce pesticide-free vegetables using vermin compost and other organic fertilizers. The study investigates consumers’ awareness and perceptions of pesticide residues in vegetables. A survey was conducted at the local market in Mymensingh, Gazipur, and Dhaka city. In total. 200 sample respondents were collected. Data were analyzed using descriptive methods. There was a substantial heterogeneity in preferences across consumers. The consumers were aware of the health risks associated with vegetables produced using pesticides and chemical fertilizers. More than 60 percent of respondents thought that vegetables are usually contaminated at the farm or production level using excessive pesticides. Most of the consumers knew the effects of pesticide-borne health risks and suggested to ban some pesticides and monitoring the use of others. Consumers considered pesticide residue-free vegetables as being safer, healthy, no harmful effects, better taste, more nutritive value, and good for the environment, and would like to pay a premium for those products. Media particularly television and newspapers can play an important role in creating awareness about food safety among the producers and consumers. Government programmes on food safety should be channeled through television and newspapers where the majority of the people get their information. Policy measures should include creating awareness concerning the relevance of production, and consumption through effective marketing strategies and educational awareness. Res. Agric. Livest. Fish. Vol. 11, No. 1, April 2024: 25-33